Crossing the color line : race, parenting, and culture - Reddy, Maureen T. (Rutgers University Press, 1994)
"Why do white people have vaginas?" asks Maureen Reddy's two-year-old son. "Why do boys have curly hair?" These are the questions Reddy grapples with on her journey, as a white mother of black children, toward an internalized understanding of race - particularly whiteness - and of racism. Moving from memoir to race theory, to literary analysis, to interviews with friends, Reddy places this personal journey in a broad cultural context. Reddy writes as a racial "insider" who stands outside accepted racial arrangements, a position that can afford unique insight into the many contradictions of those arrangements. She addresses attempts to cross the color line that divides blacks and whites; the meeting points of whiteness and blackness; the politics of feminism and anti-racism; loving blackness; mothering black children; racism in schools; and relationships among black and white women. Our culture is permeated by color. And whether we can sort out racial divisions will, Reddy feels, determine whether we survive as a society
Keywords: Multiracial children -- United States -- Case studies.; Mothers of multiracial children.; Parents of multiracial children.; Parent and child -- United States.; Racism -- United States.; Parent and child.; Families.; Nuclear families.; Prejudices.; Parent-Child Relations; Race Relations; Family; Prejudice; Nuclear Family; United States; Enfants métis -- États-Unis -- Études de cas.; Mères d'enfants métissés.; Parents et enfants -- États-Unis.; Racisme -- États-Unis.; Parents et enfants.; Familles.; Préjugés.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Prejudices; Nuclear families; Families; Mothers of multiracial children; Parent and child; Parents of multiracial children; Racially mixed children; Racism; Rassenfrage; Interethnische Ehe; Kind; USA; Case studies